PENGARUH SCREEN TIME TERHADAP DISIPLIN BELAJAR SISWA KELAS V SD RADEN RAHMAT - Tissalaras Santi; Aprilia Dwi Ismawati; Qori Ulil Qur'aini; Anna Roosyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of screen time on the learning discipline of fifth-grade students at Raden Rahmat Elementary School in the Society 5.0 era. The study used mixed methods with quantitative and qualitative approaches. The study subjects were 51 fifth-grade students from classes VA and VB. Data collection techniques were conducted through questionnaires and documentation. Quantitative data were analyzed using a simple linear regression test, while qualitative data were analyzed descriptively based on students' digital device usage activities. The results showed that screen time significantly influenced student learning discipline, with a significance value of 0.000 < 0.05 and a coefficient of determination (R²) of 0.358. This indicates that screen time contributed 35.8% to student learning discipline, with the remainder influenced by other factors. The results also showed that the most common digital device use activities for students were social media or chat and gaming. Therefore, uncontrolled digital device use can impact student learning discipline. Conversely, appropriate and productive use of digital devices can support learning and help form better study habits. Keywords: screen time 1, learning discipline 2, elementary school students 3, gadgets 4, Society 5.0 5.